Statement received from P.O.U.M.
DE06-01-001 STATEMENT RECEIVED FROM P.O.U.M. After the "May Days" in Barcelona, the counter-revolutionary elements in the Spanish anti-fascist camp, who have at their head the P.S.U.C., continued even more vigorously the suppression of the revolutionaries. Their main attack was directed against the P.O.U.M. They forced first of all the suppression of "La Batalla", central organ of P.O.U.M., and continued with an attack upon its editor, Comrade Gorkin, International Secretary of the Party, for "incitement to rebellion". On June 16th, an order was issued for the arrest and detention of the Executive Committee of P.O.U.M. and of its Central Committee. Already a certain number of comrades have been imprisoned. All the measures taken by the Valencia Government conform with the line of the Spanish Stalinists and of the Stalinist Press throughout the world. This Press accuses P.O.U.M. of having provoked the events of May, because the Party accepted the historic necessity of placing itself on the side of the revolutionary workers in their struggle against the counter-revolution. It demands the imprisonment of the members of our Committees, and the suppression of the Party's Press. "Mundo Obrero" has demanded that Gorkin should be shot. ''Treball" before the suppression of "La Batalla" demanded in its issue of June 15th the death penalty for the accused and the imprisonment of the other leading members of P.O.U.M. It is a clear frame-up by the Stalinist organisations, who seek to destroy P.O.U.M., the only Marxist party fighting in Spain for the Revolution and for Socialism. The international proletariat must express its complete solidarity with P.O.U.M. In defending this party we are defending the international proletarian revolution, we are defending Socialism. International Secretariat of Press and Propaganda, P.O.U.M. Barcelona, June 17th, 1937. 206/3/5/11/2